2022
DOI: 10.3390/ijms23073932
|View full text |Cite
|
Sign up to set email alerts
|

Psychic Life-Biological Molecule Bidirectional Relationship: Pathways, Mechanisms, and Consequences for Medical and Psychological Sciences—A Narrative Review

Abstract: Today, it is possible to investigate the biological paths and mechanisms that link mental life to biological life. Emotions, feelings, desires, and cognitions influence biological systems. In recent decades, psychoneuroendocrinoimmunology research has highlighted the routes linking the psyche–brain–immune systems. Recently, epigenetics research has shown the molecular mechanisms by which stress and mental states modulate the information contained in the genome. This research shapes a new paradigm considering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 154 publications
0
6
0
Order By: Relevance
“…Analyzing the types of personalities, Jung differentiated them based on the complex cognitive functions, including thinking, filing, sensation, intuition, and aesthetical judgment [23]. This approach assumes significant overlapping between concepts of cognitive and psychological functions, with the last one covering the areas of emotions and behavior [24,[68][69][70][71]. The expressions psychological functions (PFs), faculties, abilities, agents, states, conditions, and types are widely used in psychological sciences and to a lesser degree, in clinical practice.…”
Section: Link Of Physiological and Psychological Functionsmentioning
confidence: 99%
“…Analyzing the types of personalities, Jung differentiated them based on the complex cognitive functions, including thinking, filing, sensation, intuition, and aesthetical judgment [23]. This approach assumes significant overlapping between concepts of cognitive and psychological functions, with the last one covering the areas of emotions and behavior [24,[68][69][70][71]. The expressions psychological functions (PFs), faculties, abilities, agents, states, conditions, and types are widely used in psychological sciences and to a lesser degree, in clinical practice.…”
Section: Link Of Physiological and Psychological Functionsmentioning
confidence: 99%
“…This does not make much sense either, since the days when the CNS was thought to be hermetically sealed off from the “actual” immune system are many years behind us. Better to emphasize the interactive relationships between the neuronal, endocrine and immunological regulatory systems ( Bottaccioli et al, 2022 ). Here, although there are barriers between the CNS and the rest of the body, there is also intensive communication across these boundaries ( Miller and Raison, 2016 ).…”
Section: Neuroinflammatory Processes Of the Central Nervous Systemmentioning
confidence: 99%
“…In addition to activation by, for example, pathogen entry into the CNS ( Boche et al, 2013 ; Bernaus et al, 2020 ; Mattei and Notter, 2020 ; Deng et al, 2020 ), the immune response can also be initiated from the periphery ( Miller and Raison, 2016 ; Kim and Won, 2017 ; Gonçalves and De Felice, 2021 ; Bottaccioli et al, 2022 ). This means, on the one hand, that forms of psychological stress through activation of an immune response, for example, via the autonomic nervous system, could trigger a neuroinflammatory process in the CNS and, on the other hand, that tissue damage elsewhere in the body through the initiation of an immune response could also be responsible for a neuroinflammatory process in the CNS ( Loonen, 2023 ).…”
Section: Neuroinflammatory Processes Of the Central Nervous Systemmentioning
confidence: 99%
“…Neuroimmune dysregulation is well-documented in clinical studies of neuropathology and is observed in response to ELS (68,186,187), and neurodevelopmental (188) and psychological (189)(190)(191) disorders. In fact, Bottaccioli et al (2022) proposed that the "neuroendocrine-immune" network is a central molecular mediator between psychosocial stress and the psyche (192). Accordingly, preclinical models have demonstrated that chronic stress consistently induces microglial activation and proinflammatory cytokine signaling in key brain regions involved in psychiatric disorders (187).…”
Section: The Neuroimmune System: a Link Between Mal And The Hpa Stres...mentioning
confidence: 99%